Control of a riser through the dynamic of the vessel. Issue 9 (1st September 2016) - Seghour, L.; Khemmoudj, A.; Tatar, N.-e.
Abstract : In this paper, we prove an exponential decay result for the energy associated to a flexible marine riser with vessel dynamics. By applying a control at the top boundary of the riser we shall attenuate its vibration in a fast manner. The method is based on the multiplier technique. The riser is modeled as a viscoelastic beam with a (slightly perturbed) standard relaxation kernel.